An Analytical Look at the Importance of a Legal Organization for the International Electronic Commerce Arbitration Body: Comparative Study between a Draft Law on Arbitration in the UAE and the French and English Laws - Azab Alaziz Alhashemi (Journal of Law and Legal Reform, 2022)
This study provides theoretical and practical viewpoints regarding the law required to be applied to proceedings in the field of international commercial arbitration. The Emirati arbitration has been compared under UAE, French, and English laws. The regulations, rules and procedures of international arbitration bodies, institutions and chambers have also been undertaken in this study. This study presents the subject that was not covered from theoretical and practical viewpoint. By discussing the international electronic commerce arbitration body, this study provides insights for researchers, arbitrators, lawyers, judges with the emphasis given to all the English and French Arbitration Act along with the rules and regulations of national and international arbitration institutions and chambers. Similarly, the importance of this issue lies in the importance of arbitration as an alternative means to litigation to settle disputes. When the role of the arbitration board arises from the agreement of the parties to the arbitration dispute and from what is stated in the arbitration contract or arbitration document in the rules that obliges the parties to the arbitration to sign an arbitration document at the beginning of the proceedings. Therefore, proceedings begin because a party to the arbitration dispute expressed its desire to settle the dispute by arbitration, i.e. from the time of the request for arbitration until the award is issued in its final form.